Asykāliyatu Nuṭqil Ḥurūf Al ‘Arabiyyah Laday Ṭalabati Madrasati Tarbiyatil Qur’an: Tahlīl Taqābulī bayna Al-Lugah Al ‘Arabiyyah wa Al-Lugah Al Indūnīsiyyah fī Mustawā Al Fūnīm - Kamal Yusuf; Sri Indah Ayu Damayanti (University of Darussalam Gontor, 2019)
AbstractIndonesian learners of Arabic frequently encounter problems when learning Arabic language and its phonetics. The difficulties arise for there are differences between Arabic and Indonesian sound system. This article aimed to explore the learners’ difficulties in learning the Arabic sounds. Some learners of TPQ Al Muhajirin Sidayu Gresik were participated in this study. To conduct this research, the researcher used descriptive and contrastive approach and to collect the data by using a reading test of Arabic phonemes and interview were employed. This study revealed that the learners faced difficulties in pronouncing the Arabic consonants in which were influenced by their Indonesian language. To overcome those problems, the learners used the following strategies, i.e. pronouncing the same phonemes as in ح[ħ] and خ[x], pronouncing similar phonemes as in س [s] and ش [ʃ], pronouncing phonemes by changing the phonemes in order to make it easier to utter as in ث [q] to س [s]. This study offers a recommendation for overcoming learners’ problems in pronouncing the Arabic sounds.Keywords: Arabic phonology, Arabic teaching, contrastive analysis, pronunciation.أشكالية النطق الحروف العربية لدى طلبة مدرسة تربية القرآن: التحليل التقابلي بين اللغة العربية واللغة الإندونيسية في مستوى الفونيمكمال يوسف، سري إنداه أيو دمايانتيالجامعة الإسلامية الحكومية سونان أمبيلkamalinev@gmail.com, sriindahatudamayanti@gmail.comملخصإن المتعلمون الإندونيسيون يوجهوا المشاكل كثــيرا عند تعلم اللغة العربية و بالخصوص فى مجال علم الصوتيات (phonetics)، و تظهر الصعوبات لوجود الاختلافات بين نظام الصوت العربي و الإندونيسي. فيهدف هذه المقالة إلى استكشاف صعوبات و مشكلات المتعلمين فى تعلم الأصوات العربية، و اشتركت الطلبة من المدرسة لتعلم القرآن